Cost Estimation of Painting Works in Nigeria Using Algorithmic Equations - , Stanley Chukwudi Ugochukwu, Olusola, Ogunsina, Obinna Enem Udoka, Raymond Chike Enenmoh (Archives of Current Research International, 2020)
Inaccurate cost estimation of painting works often leaves a client dissatisfied and mars the professional expertise of the quantity surveyor. This is because either excess quantity of paint is left behind after completion of the work or the paints purchased and budget allotted for the project is unable to finish the work. To this end, this study developed algorithmic equations for estimating the cost (material and labour) of painting works using the common types of paints in Anambra and Enugu state of south-east Nigeria and also validated them using current market rates. This was achieved via identifying the types and peculiar features of the common paints used in the study area, determination of the average quantity of paint needed per square meter (to assess the material constant for the paints identified) and assessing the labour constant for the paints identified. Dulux, Homepride, Intercolour, Sharon (Vineyard) and Fine coat were among the common paint brands identified through market survey, interviews with the paint manufacturers, suppliers, painters and construction professionals and physical observation. Dulux was adjudged the most durable. Though quite expensive, it allows for creativity and flexibility and has an aesthetically pleasing outlook. The materials and labour constants were generated by physical observation, via a work study. The algorithmic equations developed are as follows: Up = Mc+ Lc; Mc = YAm x Cp; Lc = Y x Lp (thus: Up = YAm x Cp + YLp), where: Up = painting cost, Mc = Material cost, Lc = Labour cost, Y = Area of building to be painted, Am = Average quantity of the material per square meter (material constant), Cp = Cost of material per meter square, Lp = Cost of labour per square meter (labour constant). Validation of the model using current market rates of the last quarter of 2019 in the study area indicates that painting a wall of total area= 115.29 m2 using Sharon texcote paint for instance will cost N64,500. These equations not only have time saving potentials, they are also reliable when used for costing painting works involving the brand of paints surveyed. However, their efficacy relies heavily on accurate measurement of area of walls to be painted. These models are recommended for use by practicing quantity surveyors to generate feasibility cost estimates for painting works and shorten pre-contract time for both private and public clients.